The Role of Healthy Lifestyle and Attitude in mediate Threat Environment and Use Product to Intention to Buy Green Food for Gen Z - Intan Cantika Sari; Muzakar Isa (SEAN Institute, 2026)
This study aims to analyze the influence of Environmental Threats and Product Usefulness on Green Food Purchase Intention among Generation Z, with Healthy Lifestyle and Attitude toward Green Products as mediating variables. The study respondents consisted of 300 Generation Z consumers aged 17–28 in Indonesia who had purchased local food products from MSMEs, using a purposive sampling technique. Data analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that Environmental Threats positively influenced Healthy Lifestyle and Attitude toward Green Products, but had no direct effect on Green Food Purchase Intention. Product Usefulness positively influences Healthy Lifestyle, Attitude, and Green Food Purchase Intention. Attitude toward Green Products was shown to positively mediate the influence of Environmental Threats and Product Usefulness, while Healthy Lifestyle mediated negatively. These findings confirm the important role of attitudes and lifestyle in influencing green food purchasing decisions among Generation Z.